Versos Líricos en la Epigrafía Latina: el endecasílabo Falecio - Carande Herrero, Rocío (2019)
En la epigrafía latina, los versos líricos son muy minoritarios, y entre ellos apenas hay una presencia apreciable del endecasílabo falecio. Los epígrafes en versos líricos suelen inspirarse en la poesía culta, aunque no necesariamente
In Latin epigraphy, lyric verses are very rare, and among them there is hardly a significant presence of the Phalaecian hendecasyllable. The epigraphs in lyric verses are usually inspired by learned poetry, although not necessarily in poems composed in the same meter.
Keywords: Epigrafía; Poesía lírica; Lengua latina